Generation of tonalitic and dioritic magmas by coupled partial melting of gabbroic and metasedimentary rocks within the deep crust of the Famatinian magmatic arc, Argentina - Otamendi, Juan Enrique (2009)
The source regions of dioritic and tonalitic magmas have been identified in a deep crustal section of the Famatinian arc (Sierras Pampeanas of western Argentina). The source zones of intermediate igneous rocks are located at the transition between a gabbro-dominated mafic unit and a tonalite-dominated intermediate unit. In the upper levels of the mafic unit mafic magmas intruded into metasedimentary wall-rocks, crystallized mainly as amphibole gabbronorite and caused the partial melting of the surrounding metasediments. In turn, the leucogranitic melts sourced from the metasedimentary rocks intruded into the newly crystallized but still hot mafic layers and catalysed the process of partial melting of the gabbroic plutonic rocks. The gabbroic rocks became mafic migmatites comprising amphibole-rich pyroxene-bearing mesosomes and leucotonalitic veins. Significantly, most of the mafic migmatites have isotopic compositions [87Sr/86Sr(T) < 0.7063 and εNd(T) = -0.94 to +2.24] similar to those of the gabbroic rocks and distinct from those of their complementary leucotonalitic veins [87Sr/86Sr(T) = 0.7075-0.7126 and εNd(T) < -2.65], providing evidence for the idea that melting of the mafic rocks was triggered by the intrusion of leucogranitic anatectic melts [87Sr/86Sr(T) = 0.715 and εNd(T) = -6.21]. Mass-balance calculations show that the model reaction plagioclase + amphibole + leucogranitic melt → leucotonalitic melt + clinopyroxene ± orthopyroxene can better explain the partial melting of the gabbroic rocks. Based on field observations, we argue that the coalescence of leucotonalitic veins in the mafic migmatites led to breakdown of the solid matrix to form melt-dominated leucotonalitic pools. However, the leucotonalitic veins that crystallized before leaving behind the mafic migmatitic rock are chemically (elemental and isotopic) more evolved than the dioritic and tonalitic rocks. We envisage that once detached from their source region the leucotonalitic magmas were able to react, commingle and mix with entrained fragments of both mafic and metasedimentary rocks. This process gave rise to melts that became tonalitic and dioritic magmas. This study concludes that the generation of intermediate magmas is a multistage process with three critical steps: (1) influx and emplacement of hydrous mafic magmas into a deep crust containing metasedimentary country rocks; (2) physically and chemically coupled melting of mafic and metasedimentary rocks, leading to the formation of a leucotonalitic vein and dyke system that coalesces to form leucotonalitic or tonalitic magma bodies; (3) retrogression of the leucotonalitic magmas by partially assimilating entrained fragments of their mafic and metasedimentary precursors. The dimensions of the source zone seem to be insufficient to generate crustal-scale volumes of intermediate igneous rocks. However, the Famatinian paleo-arc crust would expose only those magma source zones that were still active during the tectonic closure of the arc. Ultimately, a time-integrated perspective indicates that early active source zones were cannibalized during the downward expansion of the plutonic bodies already dominated by intermediate plutonic rocks.